CAPACITY RANGE CALCULATION (Perner's Contacts, 2019)
The aim of this paper is to use a new capacity parameter called capacity range for evaluation of individual operational concept on the same line before and after planned modernization. The paper uses a new capacity parameter called capacity range. The methodology of capacity range counting is based on one main number, but it takes more aspects. It deals with the operational facility occupancy rate, with the identifying of the bottleneck, with the simulation problems solved in the simulation program SimuT and with the quality aspect of capacity. It creates the link between capacity quality and quantity, between the displayed Ishikawa diagram and the possibility of the wrong operational concept selection. The definition is explained and then the parameter is calculated for a selected section of Týniště nad Orlicí – Choceň. The capacity range is counted for current conditions (single track line, old equipment) and then for comparison for future conditions (double track line, new safety equipment). Capacity range, expressed as dependence of the number of trains on average delay increment, is a useful capacity parameter particularly for coherent railway sections with remote traffic control.
Keywords: capacity parameter; trains; range calculation